Transfer effects in gender assignment and gender concord in L3 Swedish: A case study - Kamil Długosz (Moderna Språk)
This case study examines transfer effects in the acquisition of grammatical gender in L3/Ln. A learner of L3 Swedish, who had previously acquired two grammatical gender systems: one in his native Polish and the other in his non-native Norwegian, participated in three tasks: an online gender decision task, an offline gender decision task, and a speeded acceptability judgement task on determiner phrases (indefinite article + noun). Accuracy scores in all three tasks reveal robust transfer from Norwegian, but not from Polish. The transfer from Norwegian determines two processes inherent to grammatical gender, i.e. gender assignment and gender concord. However, response latencies in the online gender decision task point to competition between the Norwegian and Swedish gender systems at the level of gender retrieval, suggesting that target-like gender representations in Swedish are developing. Since transfer is traditionally claimed to be situated at the level of linguistic representation, it is assumed that the learner in this study temporarily developed a shared grammatical gender system for Norwegian and Swedish.